When aerial surveys will not do: grey seal pup production in cryptic habitats of Wales. (September 2014) - Stringell, Thomas B.; Millar, Colin P.; Sanderson, William G.; Westcott, Stephen M.; McMath, Mandy J.
<x content-type="archive" xml:space="preserve">Abstract</x> Grey seals (Halichoerus grypus) are a species of conservation concern that require Marine Protected Area management and population status assessment under the EU Habitats Directive. Aerial surveys are commonly used to monitor grey seal pup production at their globally important UK colonies. However, in Wales more than half of pups are born in cryptic breeding habitats such as sea caves. These cryptic habitats preclude the use of aerial monitoring methods and necessitate ground-based counts, which are costly in resources. In this study, we compare a ground-based pup production census with a reduced effort plot-sampling survey to estimate pup production, derive a total population size and assess cost effectiveness. Pup production in North Wales was estimated at 91 (95% confidence interval: 70–112) by the plot-sampling design and was a good approximation of the 'true' value of 96 derived from the census. The total population size in North Wales was estimated at between 242 and 307 grey seals. The plot-sampling design reduced survey effort by 46% and saved 30% on logistical costs compared to the full census. We outline the suitability of this method as part of a monitoring programme for grey seal pup production and suggest our approach may be applicable to other regions where grey seals use cryptic breeding habitat.